Interaction Reaction Between Different Sowing Date and Weed Management Methods in Drum-Seeded Boro Rice (Oryza sativa L.) - Bera, P. S.; Bandyopadhyay, S.; Kundu, C. K.; Bandopadhyay, P.; Pramanick, B. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during boro seasons of 2004-05 and 2005-06 to find out the effects of four different date of sowing and three non-chemical weed control methods and also their interaction effects on weed flora, yield and economics of drum seeded bororice at BCKV, Mohanpur, Nadia, West Bengal, India in a split plot design. The sowing of rice was done under puddled condition by using drum-seeder, which is an upgraded device for rice sowing. Sowing of rice on 15th December produced minimum weed density and biomass at both of the observations, maximum % of effective tillersand B:C ratiocompared to other dates of sowing. Though the highest grain (5.19 t ha-1) and straw (5.65 t ha-1) yields obtained from 1st December sowing, but itwas closely followed by 15th December sowing. Amongst non-chemical weed control methods, hand-weeding gave lowest weed population and dry matter m-2 at 30 and 60 DAS, which were statistically comparable with mechanical-weeding with Japanese paddy weeder. On the other hand, mechanical-weeding produced highest grain and straw yield as well as B:C ratio. In case of interaction effects of the treatments, 15th December sowing coupled with hand weeding gave minimum weed population m-2 followed by 1st December sowing with hand weeding treatments at both 30 and 60 DAS. Sowing of drum-seeded rice on 1st December along with weeding by using Japanese Paddy Weeder produced higher grain yields (6.07 t ha-1), net return (` 29265) and B:C ratio (1.41) ascompared to other treatment combinations under the experiment.